Slavic World in the Book Collection of Count G.A. Stroganov - Irina A. Poplavskaya; Galina I. Kolosova; Evgenia V. Ablogina (Studia Litterarum)
The article examines the Russian aristocrat and diplomat G.A. Stroganov’s perception of the ideas of Slavic unity on the material of his library. Pan-Slavic ideas are presented through their interpretation in Russian, French and Common Slavic cultural consciousness as well as in the one of the collection’s owner. The authors of the books conceptualize the Russian version of Pan-Slavism as centralizing and patronizing other Slavic communities. The centripetal and centrifugal tendencies in the Slavic world are described on the material of Russian, Ukrainian, Polish, Czech (Bohemian), and Serbian literature and history. The article discusses ideas of Pan-Slavism in connection with the practice of nation-building of the 19th century, the ideas of national revival in Poland and Bohemia, the awareness of the Common Slavonic and national identity of individual communities. The authors of the article reveal ideas of Russian Pan-Slavism, Polish Messianism and Czech Austro-Slavism in terms of designing the Slavic cultural community.